2022
DOI: 10.1155/2022/2337933
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil Replacement with Poultry Oil in the Diet of Tiger Puffer (Takifugu rubripes): Effects on Growth Performance, Body Composition, and Lipid Metabolism

Abstract: Booming fish farming results in relative shortage of fish oil (FO), making it urgent to explore alternative lipid sources. This study comprehensively investigated the efficacy of FO replacement with poultry oil (PO) in diets of tiger puffer (average initial body weight, 12.28 g). An 8-week feeding trial was conducted with experimental diets, in which graded levels (0, 25, 50, 75, and 100%, named FO-C, 25PO, 50PO, 75PO, and 100PO, respectively) of FO were replaced with PO. The feeding trial was conducted in a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
6
1
1
Order By: Relevance
“…However, it should be noted that dietary MO increased the moisture content in the liver. The increase of lipid content by dietary MO was consistent with a previous study on PO substitution for FO in tiger puffer [ 50 ]. The increase of liver moisture content could be related to the (although not significant) decrease of lipid content.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, it should be noted that dietary MO increased the moisture content in the liver. The increase of lipid content by dietary MO was consistent with a previous study on PO substitution for FO in tiger puffer [ 50 ]. The increase of liver moisture content could be related to the (although not significant) decrease of lipid content.…”
Section: Discussionsupporting
confidence: 91%
“…Specific to tiger puffer, limited studies have shown that soybean meal and fish protein hydrolysate can replace a certain percentage (30% and 42.8%, respectively) of FM in tiger puffer diets [ 33 , 50 ]. As for the application of alternative lipid sources in tiger puffer diets, our previous studies have shown that PO and soybean oil can replace 100% added FO in the diets of tiger puffer [ 50 ]. That was partly why PO was further tested in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish grew normally during the whole experiment [ 25 ]. The average fish body weight at the end of the growing-out period and FO-finishing period was 41.99 g and 82.37 g, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that using soybean oil as the sole lipid source could reduce the growth performance of tiger puffer [35]. However, partial or complete MFO replacement with poultry oil did not affect the growth performance of tiger puffer [36]. The present study was aimed at comprehensively evaluating the efficacy of MFO replacement with LD or BFO in tiger puffer diets, in terms of growth, body composition, fatty acid composition, lipid metabolism, fillet quality, and flavor organic compound profile.…”
Section: Introductionmentioning
confidence: 85%